Exploring the Impact of Talent Management and Career Development on Employees’ Performance in Higher Education - Khan, Mukramin (Journal of Development and Social Sciences, 2025)
In education development, several factors are involved in determining the pathways that are critical in providing opportunities for ensuring the voyage from survival to development. In this regard, the talent management and career development are used as significant tools for inspiring the employees toward the assigned tasks and responsibilities overwhelmed at developing positive outcomes in competitive situations. These phenomena are significant for augmenting performances by using the intrinsic motivation and commitment as gears for realizing the diverse outcomes, counts for managing desired success. In order to examine impact of talent management and career development upon employees’ performance, data was collected from teachers, hailing from southern region, KP, Pakistan by using survey approach. The literature and questionnaire were analyzed by using diverse procedures. The results provide significant information for decisions about variables to ensure the required generalizability. It is suggested that institutions should be more focused on these factors for realize desired outcomes